Local loop unbundling in the UK does not affect broadband penetration - but it does lead to better service - Mattia Nardotto (DIW Economic Bulletin, 2016)
Under an open access policy, incumbent broadband providers in all EU countries are required to let new market entrants access their networks through bitstream or local loop unbundling (LLU). This type of regulatory provision aims to increase competition among all broadband providers, and is strongly recommended in markets where the prohibitively high cost of setting up a distribution network means that market power is concentrated in the hands of a few players - or even one single player (such as in the case of telecommunications). This analysis uses data from the UK to investigate whether such a policy stimulates market entry and broadband penetration and/or leads to an increase in broadband quality. In contrast to what is commonly believed LLU does not increase internet penetration significantly or sustainably. It does, however, stimulate market entry as well as investments that substantially increase service quality. Thus this open access policy does not contribute to a digital divide in access. Although these results are based solely on experiences in the UK, they do point to the general advantages of infrastructure-based competition (based on LLU) over service-based competition (based on bitstream).
Keywords: D22; K23; L43; L51; L96; 330; regulation; competition; entry; telecommunications; broadband; local loop unbundling